RIPK3 Induces Cardiomyocyte Necroptosis via Inhibition of AMPK-Parkin-Mitophagy in Cardiac Remodelling after Myocardial Infarction. (28th March 2021) - Zhu, Pingjun; Wan, Kun; Yin, Ming; Hu, Peng; Que, Yifan; Zhou, Xin; Zhang, Lei; Li, Tianzhi; Du, Yingzhen; Xu, Guogang; Fang, Xiangqun
Abstract : Receptor-interacting protein 3- (RIPK3-) modulated necroptosis plays a critical role in cardiac remodelling after myocardial infarction (MI). However, the precise regulatory mechanism is not fully elucidated yet. In the present study, we showed that RIPK3 expression was upregulated in myocardial tissue after MI in a mouse model by coronary artery ligation, as well as in the cardiomyocytes following hypoxic injury in vitro . The increase of RIPK3 expression was found to be accompanied by severe cardiac remodelling, cardiac dysfunction, and higher mortality. Elevated RIPK3 expression subsequently abrogated the AMPK pathway that was accompanied by inhibition of Parkin-mediated mitophagy. Loss of mitophagy increased the opening of mitochondrial permeability transition pore (mPTP), which ultimately induced the cardiomyocyte necroptosis. In contrast, genetic ablation of Ripk3 induced the AMPK/Parkin-mitophagy pathway, favouring a prosurvival state that eventually inhibited mPTP opening and induced the necroptosis of cardiomyocytes in the post-MI cardiac remodelling. In conclusion, our results revealed a key mechanism by which necroptosis could be mediated by RIPK3 via the AMPK/Parkin-mitophagy/mPTP opening axis, which provides a potential therapeutic target in the management of heart failure after MI.